The influence of city branding, city image, and accessibility on the decision to visit Semarang City - Wibowo, Bernadet Ekaristi; Tan, Natascha Venecia; Susilo, Clarissa Listya (Journal of Tourism, Culinary, and Entrepreneurship (JTCE), 2025)
Semarang City possesses great tourism potential due to its unique cultural and natural wealth however, challenges remain in developing its tourism destinations, particularly in creating an appealing city image and increasing visitor numbers. This study examines the impact of city marketing, city image, and accessibility on tourists' decision to visit Semarang. A quantitative approach was used to collect data through a questionnaire survey of 384 tourists who had visited Semarang in the past year. Data analysis was performed using SPSS, including validity and reliability tests and hypothesis testing using multiple linear regression. The results indicate that all three variables: city branding, city image, and accessibility have a positive and significant effect on tourists' decision to visit Semarang. The t-test results showed that the significance level of each variable was less than 0.05, and the regression model explained a large part of the variance in visit decisions. The discussion highlights that strengthening the city image through effective branding and improved accessibility can increase the attractiveness of Semarang as a tourist destination, thereby attracting more tourists to visit. These findings provide practical suggestions for city managers to improve the success of tourism strategies by focusing on these key factors.